Newspaper production as a teaching resource in science classes in youth and adult education (EJA) - Santana, Isabel Cristina Higino (2021)
This research presents an excerpt from a monographic work that investigated the perception of EJA students about the production of a newspaper as a didactic tool for science teaching with a focus on environmental education. The qualitative descriptive approach research included participants from the EJA of Uruburetama -CE. Lectures were held on the environmental issue and the production of school newspapers. The report was the instrument for collecting the data, which was subsequently analyzed through content analysis. It was noticed that the proposal to prepare a newspaper as a classroom activity in the EJA class promotes interaction, autonomy and student learning. Adapting methodologies and didactic resources to EJA classes, aiming at their learning is one of the alternatives of valuing the student, mainly, as a critical subject in their training process.